Information Cascades and Threshold Implementation: Theory and an Application to Crowdfunding - CONG, LIN WILLIAM; XIAO, YIZHOU (Journal of Finance, 2024)
ABSTRACT Economic interactions often involve sequential actions, observational learning, and contingent project implementation. We incorporate all‐or‐nothing thresholds in a canonical model of information cascades. Early supporters effectively delegate their decisions to a “gatekeeper,” resulting in unidirectional cascades without herding on rejections. Project proposers can consequently charge higher prices. Proposal feasibility, project selection, and information aggregation all improve, even when agents can wait. Equilibrium outcomes depend on crowd size, and project implementation and information aggregation achieve efficiency in the large‐crowd limit. Our key insights hold under thresholds in dollar amounts and alternative equilibrium selection, among other model extensions.